OP0273 A retrospective database study of one-year adehernce and persistence with pharmacological therapy among fibromyalgia patients in israel. (15th June 2017) - Weitzman, D; Shor, D Ben-Ami; Dahan, S; Bar-On, Y; Shalev, V; Chodick, G; Amital, H
Abstract : Background: Fibromyalgia (FM) is a chronic debilitating disorder characterized by widespread musculoskeletal pain often accompanied by fatigue, allodynia and hyperalgesia. Literature is scarce regarding adherence to pharmacologic treatments available for FM patients. Objectives: To assess one-year persistence and adherence with therapy among patients with FM and to identify factors associated with therapy discontinuation. Methods: Using the comprehensive computerized database of Maccabi Healthcare Services, a large healthcare services provider in Israel, all adults (≥21 yrs) diagnosed with FM between 2008 and 2011 were identified. FM medications included the anti-convulsant pregabalin, SSRI/SNRI and tricyclic antidepressants. Time to treatment discontinuation, defined as a gap of ≥120 days in medication supply days, and proportion of days covered (PDC) with FM-specific therapies during one year from the first dispense were analyzed. Multivariable logistic regression models were constructed to analyze factors associated with low (PDC <20%) and high (PDC ≥80%) adherence. Results: Overall 3932 eligible FM patients were identified, 88.7% females, mean) SD (age =49.2 (12.7). Pre-diagnosis use of medications of interest was documented in 41% of the patients. Of the remaining 2312, 56.1% were issued a prescription in the year following diagnosis and 45.0% dispensed at least on medication. One-year discontinuation reached 79.3% overall, and was highest for tricyclic antidepressants and lowest for SSRI/SNRI antidepressants (Table 1 ). Over one half of the patients (60.5%) were poorly adherent (PDC<20%) during the year and only 9.3% were highly adherent (PDC≥80%). Low adherence was less prevalent among patients diagnosed with migraines (OR=0.62, 95% CI: 0.48–0.80) or with both depression and anxiety (OR=0.55; 0.40–0.76). High adherence was positively associated with socio-economic status (p-for-trend=0.022). Conclusions: Persistence and adherence with FM therapy in the year following diagnosis is remarkably low. Further research is needed to assess ways to improve continuation with therapy among FM patients. Disclosure of Interest: None declared